Realising the Benefits of Sports and Physical Activity: The Human Capital Model (Materializando los beneficios del deporte y la actividad física: El modelo de capital humano) - Richard Bailey; Ed Cope; Daniel Parnell (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. Despite the fact that physical activity is universally acknowledged to be an important part of healthy functioning and well being, the full scope of its value is rarely appreciated.  This paper introduces a novel framework for understanding the relationships between physical activity (and specific forms of activity like sports) and different aspects of human development.  It proposes that the outcomes of physical activity can be framed as differential ‘capitals’ that represent investments in domain-specific assets – Emotional, Financial, Individual, Intellectual, Physical, and Social.  These investments, especially when made early in the life course, can yield significant rewards, both at that time and for years to come.  The paper also outlines some of the conditions necessary for the realization of Human Capital growth through sports and physical activity, focusing on the social factors that influence participation for children and young people.